Designing 21st Century Language Learning Scenario in Indonesia: A Perspective from Computer-Assisted Language Learning - Lala Bumela (Indonesian Journal of Arabic Studies, 2020)
The integration of international quality assurance standards into Indonesian higher education curricula, together with the enactment of the New Standard of Higher Education (NSHE), are creating new and significant pressures on the curriculum renewal as well as the reconstruction of course syllabus design in foreign language departments in Indonesian universities.  Just like any other units (courses) in foreign language departments in Indonesia, Academic Writing course at English Language Teacher Education (ELTE) is impacted by the new government policies.  Latest research suggest that both curriculum renewal and syllabus development project are integral part of the quality assurance system where it focuses on the transparency and accountability in curriculum design and delivery.  The key elements of the course syllabus that are made transparent and accountable, for instance, gives hints at the shifting knowledge structures, the use of new technologies, the emphasis on the development of students’ skills, and the extended responsibility being placed on students for their own learning development.  This paper reports how these key elements are inserted into a learner-centred pedagogy of academic writing at ELTE department in Indonesia in order to meet the requirements of the 21st century learning that are individual, personalized, adaptive, modular, integrated, and non-sequential.  The establishment of computer-assisted language learning environment combined with the new pedagogy of academic writing, in essence, opposes the existing traditional approaches to language learning and literacy pedagogy in Indonesia.  The entire story presented in this paper is a significant excerpt from the preliminary phase of experiment of a PhD research project conducted in Indonesia.  The insights presented in this paper should trigger a holistic reform in language teacher education in Indonesia.